New Approaches to Fetal Growth Restriction: The Time for Metabolomics Has Come - Debora Farias Batista Leite; Jose Guilherme Cecatti (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Fetal growth restriction (FGR) diagnosis is often made by fetal biometric ultrasound measurements orDoppler evaluation, but most babies are only diagnosed after birth, using the birth weight as a proxy for intrauterine development. The higher risks of neurodevelopmental delay, metabolic syndrome, and cardiovascular illness associated with FGR impose a shift on the focus during pregnancy. New methodological approaches, like metabolomics, can provide novel biomarkers for intrauterine fetal development. Recent evidence on metabolites involved with fetal growth and weight show a consistent role played by lipids (especially fatty acids), amino acids, vitamin D and folic acid. Fetal energy source andmetabolism, structural functions, and nervous system functioning need further evaluations in different populations. In the near future, the establishment of a core set of outcomes for FGR studies may improve the identification of the role of each metabolite in its development. Thus, we will concretely progress with the perspective of a translational capacity of metabolomics for this condition.